Common bean processing to obtain a protein ingredient for the plant-based market - Janice Ribeiro Lima; Tatiana de Lima Azevedo; Melicia Cintia Galdeano; Ilana Felberg; Caroline Grassi Mellinger (Brazilian Journal of Food Technology)
Abstract Common beans are cultivated worldwide and constitute a raw material for obtaining protein ingredients for novel product development, especially for the plant-based food market. They are naturally rich sources of proteins, ranging from 19% to 24%. This study aimed to define conditions for obtaining protein concentrate from common beans using alkaline extraction with subsequent acid precipitation. Parameters for alkaline extraction (pH, solid-to-water ratio, and stirring time) and acid precipitation (pH and stirring time) of proteins from common beans were defined. Four scaling-up tests were performed to validate the selected parameters (n=4). Results showed that the process should follow a protein water extraction step (water and bean flour ratio of 1:8, pH of 9.0, and 30 minutes stirring) followed by an acid precipitation step (pH of 5.5 and 10 minutes stirring) and spray drying. The protein concentrate obtained is a powder with 76.5% (± 3.76) protein on a dry basis, and the process presented a mass yield of 11.0% (± 0.91) and a protein yield of 39.7% (± 2.50). Techno-functional properties of water holding capacity (1.77 ± 0.05 g water/g), oil holding capacity (1.22 ± 0.05 g oil/g), emulsifying activity index (18.87 ± 0.35 m2/g), foaming capacity (73.33 ± 6.67%), and least gelling concentration (20.00 ± 0.00 g/100g water) of the concentrate were also determined. The process for obtaining common bean protein concentrate, including the steps of alkaline extraction and acid precipitation, was defined along with its yield and the concentrate performed similarly to that of others obtained from different types of beans in terms of techno-functional properties.